2009
DOI: 10.1177/097226290901300103
|View full text |Cite
|
Sign up to set email alerts
|

Stock Markets Integration: Examining Linkages between Selected World Markets

Abstract: In recent years, globalisation, economic assimilation and integration among countries and their financial markets have increased interdependency among major world stock markets. This increased interdependency among the worldwide stock markets may have impacts on the global investors for their assets allocation decision and on the economic policies of economies for ensuring economic stability. Hence, there is a need to study the extent of integration among the world stock markets which is the objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Globalization has linked economies worldwide and increased the interdependence of global financial markets in recent years. This increased interdependence among the global stock markets may have an impact on global investors' decisions on asset allocation and on economies as well as economic policies to ensure economic stability [11]. By using a vector auto regression model, In, Kim, and Yoon [12] examined the dynamic linkages and interactions between the Asian stock markets and their results showed that the markets became more closely linked during the financial crisis, except Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has linked economies worldwide and increased the interdependence of global financial markets in recent years. This increased interdependence among the global stock markets may have an impact on global investors' decisions on asset allocation and on economies as well as economic policies to ensure economic stability [11]. By using a vector auto regression model, In, Kim, and Yoon [12] examined the dynamic linkages and interactions between the Asian stock markets and their results showed that the markets became more closely linked during the financial crisis, except Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…The performance in US (New York) market strongly influenced Japanese market performance, but the reverse was not true before and after October 1987 crisis (Becker, Finnerty, & Gupta, 1989). Asian markets have no influence on each other in spite of existing correlation between the 12 world markets, none of them plays a dominant role (Siddiqui, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raj and Dhal (2009) found strong integration of Indian market with other markets. Siddiqui (2009) found that world stock market indices were interrelated with each other. Conversely, Nath and Verma (2003) suggested that no long run equilibrium relationship found among India, Singapore and Taiwan markets and therefore equity market of south Asian were not inter-related with each others.…”
Section: Review Of Literaturementioning
confidence: 99%